PEMANFAATAN MEDIA VISUAL DALAM PEMBELAJARAN DI TK NEGERI PEMBINA PONTIANAK SELATAN - Noviana, Desi; Ali, Muhamad; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the utilization of visual media in learning in TK Negeri Pembina Pontianak Selatan. This research uses descriptive method and using qualitative approach. The data source of this research is group B teacher of 4 people. Result of research of utilization of visual media in learning that is, activity plan of learning through steps which is done to formulate special purpose, choose and give interesting learning experience, determine and involve child in learning process, choose material, and teachers to evaluate. How teachers choose the visual media that is adapted to the material or theme and choose the media according to the child's age and learning objectives can be achieved. Types of media used by non-projected visual media magazines, magazines, booklets, notebooks. Teachers use visual media by undertaking preparation, execution, evaluation and follow-up stages. The way the teacher to evaluate at the end of the learning activities of teachers to conduct an evaluation to ask questions, whether the purpose of learning can be achieved or not. Obstacles teachers in the use of visual media that images available in magazines or books too large package. Keywords: Utilization of Visual Media, Learning Activities.